Perancangan Aplikasi Pembelajaran Huruf Hijaiyah Berplatform Android Untuk Madrasah Baca Tulis Al Quran Al-Fattah Desa Widodaren Kabupaten Ngawi - Purwanti, Ika (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2013)
ABSTRACT : The technology of today is growing so rapidly. System operation is emerging discussed today is the latest android version. Many electronic devices are already implementing this operating system. To keep pace with technological developments such people are more likely to want the simple things that can be used easily and quickly. This includes the media-based learning hijaiyah letters. There have been many other media that introduce both conventional hijaiyah letter in the form of direct learning through mentors or teachers hijaiyah letters. But for those with busy activities they like things are simple and can be used anywhere in between activities. For this reason the author wrote a thesis entitled